Rubén Astudillo y Astudillo... la ira, el silencio y el retorno (Crítica) - Astudillo Sarmiento, Juan Carlos (2025)
The poetry of Rubén Astudillo y Astudillo, one of the key authors in Ecuadorian poetry of the second half of the twentieth century, can be read from the postulates of existentialism, especially in dialogue with the thought of Schopenhauer, Heidegger, Kierkegaard, and Nietzsche, in the first instance and attending to his first collections of poems (from the late 1950s until the end of the 1979s). From the 1980s onwards, his work can be read from the ideas of mysticism, in dialogue with Russel and Paz, and from the ideas of memory and childhood, taking up Bachelard’s concepts. This article proposes this reading for the work of the poet from Cuenca.